Learning and Teaching in Adult Education Contemporary Theories - Pätzold, Henning (Verlag Barbara Budrich, 2011)
Learning is a key issue in education. Being familiar with contemporary learning theory, therefore, is an essential prerequisite for education scholars and practitioners alike.